Analysis of the effectiveness of the offensive game model in elite handball - González-García, I.; Martínez, L. C. (South African Journal for Research in Sport, Physical Education and Recreation, 2023)
The aim of the study was to identify the success variables associated with the level of efficiency established using an offensive game model during the second phase of the 2013 World Handball Championship for men in Spain. Sixteen matches were selected and 1925 units of observation were analysed, of which 8095 events were recorded using the HandballTAS tool (Handball Tactic Analysis System). The variables analysed to determine offensive effectiveness were individual actions, offensive punishment, degree of opposition, field area, location, numerical situation, and duration. The data were subjected to multivariate analysis in the form of binary logistic regression and classification tree. The classification and regression model correctly classified 81.6% of the dependent variables on offensive effectiveness (assist and numerical situation, p<0.05; field area and location, p<0.001). Offensive effectiveness increases with an assist (53%) and decreases with a shot from the wing-shots (53%), and with a 9-metre shot (65%) compared with a 6-metre shot. In respect of location, efficacy was reduced by 69% with shots in the middle zone of the goal when compared with shots in the lower zone. The probability of success was reduced by 49% in the warning of the passive play situation and 43% in the inferiority situation compared to the equality situation.